(untitled) (Journal of Namibian Studies : History Politics Culture, 2021)
This study was carried out at the Sarusungu Border Post which connects Rundu and Calai, the capital towns and administrative hubs of Kavango East Region (northern Namibia) and Southern Cuando Cubango Province (southern Angola). This study sought to understand the role of the bridgehead in informal cross-border trading activities at Rundu-Calai border post. The study employed semi-structured interviews, and 55 participants were interviewed. Outcomes indicate that the driving forces of informal cross-border trading have been: the devaluation of Angolan Kwanzas; bridge relocation; the rising demand for Angolan goods in Rundu; higher Namibian dollars leverage and failure to pay public servants’ salaries in Calai. These forces have contributed to a boom in the number of cross-border retailers, shop owners and money-changers, while also contributing to exorbitant exchange prices, a shortage of the Kwanza in Rundu and Calai, and to increasing costs of a return trip to Calai from N24 to N112. This, in turn, has led to the circumventing of legal border taxes and goods being auctioned. In conclusion, Rundu has become a hub for the suppliers of infrastructural goods used in construction, electronics and automobiles for Calai while Rundu residents find supplies of household commodities such as food in Calai.